Strategies and Implementation of Character Education Empowerment Management through Islamic Cultural Schools (Madrasah Tsanawiyah) in Dempet District - Ristanti, Yulia Devi; Banowati, Eva; Subagyo, Subagyo (Universitas Negeri Semarang, 2020)
Nowadays, character education is required to educate learners so they will be excellent individuals.Many schools take various ways to apply strategies to succeed in character education programs.Besides nurturing the characters at home, done by parents, the educational institution also plays agreat role to develop children's characters. This research used a qualitative approach. The data werecollected through in-depth interview, observation, and documentary study. The data analysis useddata reduction, display, and conclusion. The findings consisted of 1) the Islamic school characterbuildingstrategies in Dempet applied Islamic habituations. They were such as reading AsmaulHusna and reciting Al-Qur'an together in the morning before getting into the class and starting thelearning; 2) the implementation of character educational empowerment was done through Islamiccultures in Dempet district. It could be done by providing memorization tasks of Al-Qur'an verses.Every class should have different memorization level and should apply extracurricular to educate thelearners to have excellent characters, and 3) the engaged hindrances during its implementation werelacks of parents' controls. Thus, the learners tended to have bad personalities while being at schoolor home.